Lysine α-ketoglutarate reductase as a therapeutic target for saccharopine pathway related diseases - Valderrama, Gabriel Vieira; Moreira, Gabriela Alves; Arruda, Paulo (Frontiers in Molecular Neuroscience, 2025)
The saccharopine pathway (SacPath) and the pipecolate pathway (PipPath) catabolize lysine to α-aminoadipate. Although the PipPath has been highlighted as the prominent route operating in the brain, recent work has demonstrated that the SacPath plays a major role in lysine catabolism in the brain. The first two enzymatic steps of the SacPath involve the bifunctional enzyme α-aminoadipate semialdehyde synthase (AASS) harboring the lysine-ketoglutarate reductase (LKR) and the saccharopine dehydrogenase (SDH) domains that convert lysine to α-aminoadipate semialdehyde. Thereafter, the semialdehyde is converted to α-aminoadipate by α-aminoadipate semialdehyde dehydrogenase (AASADH). Mutations abolishing the enzymatic activities of LKR, SDH, and AASADH lead to the genetic diseases hyperlysinemia type I and II, and pyridoxine-dependent epilepsy (PDE), respectively. Hyperlysinemia type I accumulates lysine and causes a benign phenotype without clinical significance. Hyperlysinemia type II accumulates saccharopine, which leads to neuronal disorders and intellectual disability. PDE accumulates α-aminoadipate semialdehyde and its cyclic isomer piperideine-6-carboxylate, which binds pyridoxal 5′-phosphate, disturbs synapses, and causes seizures along with developmental disorders. Another genetic disease, glutaric aciduria type I (GA1), localizes just downstream of the SacPath and is caused by mutations abolishing the enzymatic activity of glutaryl-CoA dehydrogenase (GCDH). GA1 accumulates glutarate and 3-hydroxyglutarate, which are neurotoxic molecules that cause irreversible brain damage. Downregulation of LKR has been shown to reduce the metabolic flux through SacPath and alleviate PDE and GA1 symptoms. This review discusses the role of SacPath and its enzymes as potential targets for developing drugs to treat PDE and GA1, as well as other diseases.